Containerlab як інструмент моделювання та симуляції мереж на основі контейнеризації - Шестопалов, С. С. (ХНУРЕ, 2024)
In the last decade, containerization technologies like Docker have rapidly developed, enabling isolated execution of multiple operating environments without full hardware emulation. This approach offers advantages over traditional virtual machines by providing standardization, scalability, and automated deployment of applications while using significantly fewer resources. Containerlab addresses the challenge of deploying and interconnecting containers for complex network topologies by offering an open-source command-line tool that simplifies the creation of network labs based on containers and virtual machines. Using simple YAML files, it automates the process of creating and configuring network connections between nodes and managing their lifecycle. This paper provides an overview of Containerlab's features and demonstrates its applications in development, testing, education, security auditing, and automation.
Keywords: контейнерізація; Docker; симуляція мереж